The efficacy of lacosamide as monotherapy and adjunctive therapy in focal epilepsy and its use in status epilepticus: clinical trial evidence and experience - Bauer, Sebastian (Ther Adv Neurol Disord, 2016)
Lacosamide (LCM) is approved for anticonvulsive treatment in focal epilepsy and exhibits its function through the slow inactivation of voltage-gated sodium channels (VGSCs). LCM shows comparable efficacy with other antiepileptic drugs (AEDs) licensed in the last decade: in three randomized placebo-controlled trials, significant median seizure reduction rates of 35.2% for 200 mg/day, 36.4–39% for 400 mg/day and 37.8–40% for 600 mg/day were reported. Likewise, 50% responder rates were 38.3–41.1% for 400 mg/day and 38.1–41.2% for 600 mg/day. Similar rates were reported in post-marketing studies. The main adverse events (AEs) are dizziness, abnormal vision, diplopia and ataxia. Overall, LCM is well tolerated and has no clinically-relevant drug–drug interactions. Due to the drug’s intravenous availability, its use in status epilepticus (SE) is increasing, and the available data are promising.